PEWARNAAN TOTAL R-DINAMIS DENGAN TEKNIK FUNGSI PEWARNAAN BERPOLA PADA HASIL OPERASI COMB SISI DARI GRAF CYCLE SERTA KAITANNYA DALAM KETERAMPILAN BERPIKIR TINGKAT TINGGI - Wardani, Putu Liana; Dafik, Dafik; Setiawani, Susi (Kadikma, 2015)
Abstract. If G = (E,V) is a simple graph, connective and undirected graph that has a set of vertex (V), set the edge (E), d(v) is the degree of a v Є V(G) and d(u) is the degree of an edge u Є E(G). The number of maximum and minimum degree of the graph G is denoted respectively by Δ(G) dan δ(G). Proper k-coloring graph G is c : V(G) ᴜ E(G) to a colored set which have to fulfill the conditions of : [1.] for each v Є V(G), |c(N(v))| ≥ min[r,d(v)+ |N(v)|] dan [2.] for each e = uv Є E(G), |c(N(e))| ≥ min[r,d(v)+d(u)]. R-dynamic color number of a graph G is denoted a minimum color of k in graph. This article discuss about total r-dynamic coloring of graph . The result shows that the total r-dynamic coloring of the graph for r =1, 2, 3, ..., n. Keywords : Total Coloring R-dynamic, Edge Comb Product, High Order Thinking Skill